Peran Sosial Politik Kyai di Indonesia - Miftah Faridl (Fakultas Seni Rupa dan Desain ITB, 2007)
The social and political behavior differences among the Kyais (Islamic religious leaders) have been very much influenced by two main factors: their social position and personal capability. The former factor relates with their social position with which they drive the social changes. They function as a'cultural broker' becouse they can communicate with various social groups and accommodate each social group's interest. The latter factor deals with their capability, based on their understanding about Islamic teachings, in guiding their local Islamic believers to make their political decisions.